Quadi, Marcomanni and the Suebian Confederation in Domitian’s and Trajan’s Dacian Wars - David SORIA MOLINA (Studia Historica: Historia Antigua, 2017)
After five decades of close alliance with roman Power, in the late 1st century aD the suebian confederation split off and its eastern members, Quadi and marcomanni, entered the way of direct conflict with rome. those events were an essential part of the violent geopolitical readjustment of the Danubian space which its main display were the  Dacian wars happened under the reigns of Domitian and trajan, becoming an inflection point on the Foreign affairs of the roman Empire in Danube’s high course until the burst of the marcomannic wars more than half a century later. throughout this article we are going to enter the causes of the suebian confederation breakup, the wars sustained by Quadi and marcomanni against romans and their allies, as well as the role played by the Dacian wars and its main actors in these conflagrations and their resolution.